Association between physical activity and cancer risk among Chinese adults: a 10-year prospective study - Su, J; Jiang, Y; Fan, X; Tao, R; Wu, M; Lu, Y; Hua, Y; Jin, J; Guo, Y; Lv, J; Pei, P; Chen, Z; et al. (BioMed Central, 2022)
Background: In China, the quantity of physical activity differs from that in Western countries. Substantial uncertainty remains about the relevance of physical activity for cancer subtypes among Chinese adults.